2008
DOI: 10.1242/jcs.019281
|View full text |Cite
|
Sign up to set email alerts
|

LUMA interacts with emerin and influences its distribution at the inner nuclear membrane

Abstract: The nuclear envelope (NE) defines the border of the nucleus: an inner nuclear membrane (INM) and an outer nuclear membrane (ONM) join at the nuclear pores, which harbor the nuclear pore complexes (NPCs) that guard the entry to and exit from the nucleus. Although the ONM is continuous with the rough endoplasmic reticulum (rER), both ONM and INM have specific sets of integral membrane proteins (Schirmer and Foisner, 2007). There are ~80 known INM proteins (Dreger et al., 2001;Schirmer et al., 2003;Schirmer and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
111
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 67 publications
4
111
3
Order By: Relevance
“…Emerin directly binds more than ten known partners, suggesting a degree of biochemical complexity at the NE that rivals many cell surface structures. Among these partners are structural proteins (nesprin-1a, nesprin-2b, actin, nuclear myosin 1c, lamins, and tubulin), other INM proteins (MAN1 and LUMA), proteins involved in signaling, transcription, mRNA splicing (b-catenin, GCL, Lmo7, Btf, and YT521-B), and of course, BAF Mislow et al 2002a;Holaska et al 2003;Haraguchi et al 2004;Holaska et al 2004;Mansharamani and Wilson 2005;Markiewicz et al 2006;Wheeler et al 2007;Bengtsson and Otto 2008) (for reviews, see Bengtsson and Wilson 2004;Wagner and Krohne 2007). The biochemical purification of emerin-associated protein complexes from HeLa cell nuclei suggests emerin can form at least six distinct multiprotein complexes (Holaska and Wilson 2007).…”
Section: Lamin-binding Proteinsmentioning
confidence: 99%
“…Emerin directly binds more than ten known partners, suggesting a degree of biochemical complexity at the NE that rivals many cell surface structures. Among these partners are structural proteins (nesprin-1a, nesprin-2b, actin, nuclear myosin 1c, lamins, and tubulin), other INM proteins (MAN1 and LUMA), proteins involved in signaling, transcription, mRNA splicing (b-catenin, GCL, Lmo7, Btf, and YT521-B), and of course, BAF Mislow et al 2002a;Holaska et al 2003;Haraguchi et al 2004;Holaska et al 2004;Mansharamani and Wilson 2005;Markiewicz et al 2006;Wheeler et al 2007;Bengtsson and Otto 2008) (for reviews, see Bengtsson and Wilson 2004;Wagner and Krohne 2007). The biochemical purification of emerin-associated protein complexes from HeLa cell nuclei suggests emerin can form at least six distinct multiprotein complexes (Holaska and Wilson 2007).…”
Section: Lamin-binding Proteinsmentioning
confidence: 99%
“…The anti-receptor antibodies were cross-linked to protein-A-Sepharose (SigmaAldrich) with DMS (dimethyl suberimidate dihydrochloride; Pierce, Rockford, IL) before use. For immunoblotting the following antibodies, diluted as indicated in TBST (150 mM NaCl, 50 mM Tris-HCl pH 8.0, 0.1% v/v Tween) were used: anti-PP2A-B (1:1000; Millipore), anti-HA (1:1000; Roche Diagnostics, Mannheim, Germany), anti-FLAG (1:2000; Sigma-Aldrich), anti-β-actin (1:5000-1:10,000; Sigma-Aldrich), anti-MYC [1:1000 (Bengtsson and Otto, 2008)], anti-Smad1 (1:500; Santa Cruz Biotechnology, Santa Cruz, CA or 1:1000; Cell Signalling Technology), anti-MBP (1:1000; Cell Signalling Technology, Danvers, MA), anti-p-Smad1/5/8 (1:1000; Cell Signalling Technology), and anti-MAPK/CDK substrate (1:1000; Cell Signalling Technology). The blots were developed with appropriate HRP-conjugated secondary antibodies followed by ECL reaction.…”
Section: Antibodiesmentioning
confidence: 99%
“…20 In the meanwhile, the topological and functional characterization of LUMA showed that it contains a large hydrophilic and 4 transmembrane domains, and that the transmembrane spans are necessary for nuclear envelope targeting and homo-oligomerization. 21 In addition, it was demonstrated that LUMA interacts with lamins and emerin and is involved in the structural organization of nuclear membrane. As emerin is postulated to form complexes with different partners at NE to carry out distinct functions, 21,22 and mutation in TMEM43 could cause cardiac conduction defect, a characteristic of EDMD, LUMA can logically be considered to contribute to the pathomechanism of EDMD-related myopathy.…”
mentioning
confidence: 99%
“…21 In addition, it was demonstrated that LUMA interacts with lamins and emerin and is involved in the structural organization of nuclear membrane. As emerin is postulated to form complexes with different partners at NE to carry out distinct functions, 21,22 and mutation in TMEM43 could cause cardiac conduction defect, a characteristic of EDMD, LUMA can logically be considered to contribute to the pathomechanism of EDMD-related myopathy.…”
mentioning
confidence: 99%